SURFACE CATALYSIS OF URANIUM(VI) REDUCTION BY IRON(II) - SPECTROSCOPIC EVIDENCE FOR SORPTION AND REDUCTION - Liger E.; Charlet L.; Van Cappellen P. (My University, 1999)
Colloidal hematite (α-Fe2O3) is used as model solid to investigate the kinetic effect of specific adsorption interactions on the chemical reduction of uranyl (UVIO22+) by ferrous iron. Acid-base titrations and Fe(II) and uranyl adsorption experiments are performed on hematite suspensions, under O2- and CO2-free conditions. The results are explained in terms of a constant capacitance surface complexation model of the hematite-aqueous solution interface. Two distinct Fe(II) surface complexes are required to reproduce the data: (=FeIIIOFeII)+ (or =FeIIIOFeII(OH2)n+) and =FeIIIOFeIIOH0 (or =FeIIIOFeII(OH2)n-1OH0). The latter complex represents a significant fraction of total adsorbed Fe(II) at pH > 6.5. Uranyl binding to the hematite particles is characterized by a sharp adsorption edge between pH 4 and pH 5.5. Because of the absence of competing aqueous carbonate complexes, uranyl remains completely adsorbed at pH > 7. A single mononuclear surface complex accounts for the adsorption of uranyl over the entire range of experimental conditions.Although thermodynamically feasible, no reaction between uranyl and Fe(II) is observed in homogeneous solution at pH 7.5, for periods of up to three days. In hematite suspensions, however, surface-bound uranyl reacts on a time scale of hours. Based on Fourier Transformed Infrared spectra, chemical reduction of U(VI) is inferred to be the mechanism responsible for the disappearance of uranyl. The kinetics of uranyl reduction are quantified by measuring the decrease with time of the concentration of U(VI) extractable from the hematite particles by NaHCO3. In the presence of excess Fe(II), the initial rate of U(VI) reduction exhibits a first-order dependence on the concentration of adsorbed uranyl. The pseudo-first-order rate constant varies with pH (range, 6-7.5) and the total (dissolved + adsorbed) concentration of Fe(II) (range, 2-160 μM). When analyzing the rate data in terms of the calculated surface speciation, the variability of the rate constant can be accounted for entirely by changes in the concentration of the Fe(II) monohydroxo surface complex =FeIIIOFeIIOH0. Therefore, the following rate law is derived for the hematite-catalyzed reduction of uranyl by Fe(II), d[U(VI)]dt=-k[=FeIIIOFeIIOH0][U(VI)]ads where the bimolecular rate constant k has a value of 399 +/- 25 M-1 min-1 at 25°C. The hydroxo surface complex is the rate-controlling reductant species, because it provides the most favorable coordination environment in which electrons are removed from Fe(II).Natural particulate matter collected in the hypolimnion of a seasonally stratified lake also causes the rapid reduction of uranyl by Fe(II). Ferrihydrite, identified in the particulate matter by X-ray diffraction, is one possible mineral phase accelerating the reaction between U(VI) and Fe(II). At near-neutral pH and total Fe(II) levels less than 1 mM, the pseudo-first-order rate constants of chemical U(VI) reduction, measured in the presence of the hematite and lake particles, are of the same order of magnitude as the highest corresponding rate coefficients for enzymatic U(VI) reduction in bacterial cultures. Hence, based on the results of this study, surface-catalyzed U(VI) reduction by Fe(II) is expected to be a major pathway of uranium immobilization in a wide range of redox-stratified environments.